Prognosticating acute ischemic stroke and estimating the feasibility of mapping stroke volume to the functional outcomes using diffusion-weighted images: A systematic review protocol - Priyanka Shridharan; Tarun Gangil; Sankar Prasad Gorthi; K Prakashini (Annals of Indian Academy of Neurology, 2023)
Introduction: Diffusion-weighted image or DWI is commonly used to provide valuable and diverse information on acute stroke in tertiary care hospitals. DWI is a sensitive and accurate method for identifying the infarct core and can expose the area of cerebral infarction within a few hours of onset. This systematic review is planned to evaluate the measurement of stroke volume on DWI and correlate it with functional outcomes (modified ranking scale). Method: We have adhered to the PRISMA-P checklist to report this systematic review protocol. PubMed, Web of Science, Scopus, and TRIP (Turning Research into Practice) databases will be searched. Two independent reviewers will screen the records, extract data, and critically appraise the studies. A checklist for critical appraisal will be applied for data abstraction, and data extraction will be done using predictive modeling for systematic reviews. The risk of bias will be measured by the Prediction Model Risk of Bias Assessment Tool (PROBAST). The meta-analysis will be considered only if included studies have adequate data, and STATA statistical package version 13.1 will be used for performing a meta-analysis. A narrative synthesis will be performed if meta-analysis is not possible. Ethics and Dissemination: As this review will focus on secondary information, there is no ethical consideration required. We will disseminate our findings by publishing our analysis in a peer-reviewed journal. Protocol Registration: In Prospective Register of Systematic Reviews (CRD42019141840).